Ernährung & Sport - Kindermann W; Scharhag J (Dynamic Media Sales Verlag, 2016)
Compared to white athletes, African/Afro-Caribbean (black) athletes exhibit cardiovascular specifities. In the ECG, early repolarization is much more common. The prevalence of T-wave inversions in black athletes is present in up to 23%, and in white athletes in 2-4%. Domed ST segment elevation combined with T-wave inversion in the anterior leads is a typical finding in black athletes. In addition, left ventricular hypertrophyis more pronounced. 12-18% develop wall thicknesses >12mm (maximal 16mm) compared to 2-4% in white athletes (maximal 14mm). There are no significant differences in left ventricular end-diastolic diameter, systolic and diastolic function and the right ventricle. As early as in adolescence, black athletes reveal thicker chamber walls (maximal 15mm), and repolarization changes are more frequent than in white athletes. Similar to males, black female athletes present a greater left ventricular hypertrophy than white female athletes, and T-wave inversions are more frequent. In conclusion,the gray zone between physiological and pathological left ventricular hypertrophy is greater in black athletes.KEY WORDS: Ethnic Differences, Cardiovascular Specifities, ECG, Echocardiography, Hypertrophy